Prices for Crop and Livestock Cost-Return Budgets - Langemeier, Larry N.; Kastens, Terry L.; Jones, Rodney (My University, 1996)
A publication detailing wheat, corn, grain sorghum, and soybean price projections.
MF1013_1996-10
Keywords: MF1013; Economics; Crops; MF